2020
DOI: 10.1088/1757-899x/869/7/072051
|View full text |Cite
|
Sign up to set email alerts
|

Operational efficiency of water damless intake

Abstract: An improved hydraulic method for increasing the efficiency of operation of a damless water intake is presented. Physical picture of the movement of bottom and surface sediments during flow division in the damless water intake ABMCh (Amu-Bukhara machine channel). Analysis of the distribution of sediment along the channel of the channel showed that clay particles of suspended sediment <0.005 mm increase from the inlet to the main structure of the ABMCh from 15% to 36%. Dusty particles of suspended sediment d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 1 publication
0
42
0
Order By: Relevance
“…This study aims to study climate change and future projections for the Amu Darya basin. The Amu Darya is the largest river in Central Asia, with a catchment area of 309,000 km2 and a length of 2540 km [3][4][5][6][7]. It is a transboundary river shared by Afghanistan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aims to study climate change and future projections for the Amu Darya basin. The Amu Darya is the largest river in Central Asia, with a catchment area of 309,000 km2 and a length of 2540 km [3][4][5][6][7]. It is a transboundary river shared by Afghanistan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan.…”
Section: Resultsmentioning
confidence: 99%
“…The expected increase in water consumption here leads to competition for water at the regional and local levels between irrigation and energy, other sectors of the economy. Intensive climate warming is noted throughout Central Asia and the prospective assessment of the region's water resources, taking into account climate change, shows that none of the considered climate scenarios reflecting warming involves an increase in the available water resources [1][2][3][4][5][6][7]. The calculations obtained indicate that by 2050 the volume of river flow in the Amu Darya basin will decrease by 10-15% and in the Syr Darya by 6-10%.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the safety and sustainable operation of РS, it is recommended to: develop regulatory documents that determine the properties of water, which do not lead to wear of equipment and destruction of materials; a methodology for a comprehensive assessment of the degree of risk from the impact of a resource of inappropriate quality during the operation of the РS [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…In [8], based on many years of research, they somewhat expanded the concept of the channel process and concluded that "the channel process is understood as a constant change in the morphological structure of a river that occurs under the influence of flowing water».…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is the complexity and multifactorial nature of the course of channel processes in space and time. Especially great difficulties arise in the design of head structures with a damless water intake from the Amu Darya, the channel of which, due to the large slopes of the bottom, high flow rates and easy erosion of bottom sediments (represented by fine sandy weak soils), is subject to extremely complex intense planned and deep deformations [6][7][8]. To solve this problem, it is recommended to use physical -experimental modeling, which can give a specific forecast of channel deformations in the area of the damless water intake to the head structure.…”
Section: Introductionmentioning
confidence: 99%